PENERAPAN MODEL PEMBELAJARAN CASE BASED LEARNING BERBANTUAN SMOKELESS INCINERATOR UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI SUHU, KALOR, DAN PEMUAIAN - Nugroho, Sava Azania; Nasir, Muhammad; Islami, Nur (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2024)
This research aims to describe the application of case based learning model assisted by smokeless incinerator to improve students' critical thinking skills and to determine the difference in students' critical thinking skills between classes that apply case based learning model assisted by smokeless incinerator and classes that apply conventional learning model on temperature, heat, and expansion material at SMPN 1 Tapung Hulu. The research method used is quasi experimental with data collection techniques in the form of pretest and posttest. This study used a simple random sampling technique. The samples in this study included class VII B as the experimental class and VII C as the control class. The results of descriptive analysis in the experimental class obtained an average critical thinking ability of 79.11 in the good category, while the control class obtained an average critical thinking ability of 46.06 in the sufficient category. The results of hypothesis testing obtained 0.000 whose value is smaller than 0.05. There is a significant difference in students' critical thinking skills between the experimental class that applies the case based learning model assisted by smokeless incinerator and the control class that applies the conventional learning model on temperature, heat, and expansion material.